Chemical characterization, antioxidant, cytotoxicity, Anti-Toxoplasma gondii and antimicrobial potentials of the Citrus sinensis seed oil for sustainable cosmeceutical production - Atolani, O. (Heliyon, 2020)
There are growing concerns about the chronic and acute effects of synthetic additives such as antibacterial, fragrances, colourants and stabilizing agents used in the production of various household products. Many household products and materials including cosmetic products are reportedly suspected to be carcinogenic with some acting as endocrine disruptors among other effects. Thus, environmental-friendly alternatives such as products that are rich in bioactive phytochemicals are becoming consumers' preferred choice especially in the beauty and cosmetic sector. ‘Green’ preparation of medicinal soaps devoid of any synthetic additives was made from underutilized tropical seed of Citrus sinensis seed oil and some natural additives comprising of natural honey, Ocimum gratissimum leaves extract, Moringa oleifera seed oil and coconut oil. Precisely, the seed oil of the underexplored C. sinensis was obtained via soxhlet extraction and saponified with natural lye solution at different ratios to produce soaps of varying characteristics. The incorporation of honey and Ocimum gratissimum leaf extract provided additional antimicrobial, antioxidant and fragrance properties. Physico-chemical parameters of the oil and soaps were determined following standard procedures while the fatty acid profile of the trans-esterified oil was determined using GC–MS. The antimicrobial potential of the oil and soaps were assessed using agar diffusion method at concentrations 200 mg/mL and below. Linoleic acid (36%) and oleic acid (27%) were the most prominent in C. sinensis seed oil. The soap had antimicrobial potential comparable to commercial product. The soap samples recorded highest anti-bacteria activities (22.0 ± 1.0–23.0 ± 1.0) against Staphylococcus aureus and Bacillus subtilis and notable anti-fungi activities (18.0 ± 1.0) against Penicillium notatum and Candida albicans. Additionally, the oil showed moderate anti-parasite (anit-toxoplasma gondii) activity (EC(50) ≤ 500 μg/mL) but with improved selectivity that precludes oxidative stress while the prepared medicinal soaps exhibited remarkable antioxidant property. The utilization of these locally sourced resources will prevent the daily introduction of synthetic antimicrobial and antioxidant chemicals into the environment. The initiative avail a sustainable production of environmentally-benign cosmetic products besides conversion of waste to wealth agrees which aligns with the Sustainable Development Goals (SDGs).